Grounded : a novel - Saeed, Aisha; Al-Marashi, Huda, 1977-; Thompkins-Bigelow, Jamilah; Ali, S. K. (Amulet Books, 2023)
When a thunderstorm grounds all flights following a huge Muslim convention, four unlikely kids are thrown together. Feek is stuck babysitting his younger sister, but he'd rather be writing a poem that's good enough for his dad, a famous poet and rapper. Hanna is intent on finding a lost cat in the airport--and also on avoiding a conversation with her dad about him possibly remarrying. Sami is struggling with his anxiety and worried that he'll miss the karate tournament that he's trained so hard for. And Nora has to deal with the pressure of being the daughter of a prominent congresswoman, when all she really wants to do is make fun NokNok videos. These kids don't see to have much in common--yet. 'Told in alternating points of view, at Hurston Airport, four unlikely kids' lives are changed forever when their flight is grounded by weather following a Muslim convention.